Pendampingan Pembuatan Business Model Canvas Bagi Pengembangan Bisnis UKM Mart Teluk Pucung - Nugroho, Oki Widhi; Aji, Sonny Nugroho; Pribadi, Agustinus Yunan; Turseno, Andi; Tanisri, Roberta Heni Anggit; Apriyani; Nadia, Ainun (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Business development must be observed by business owners in order to maintain their existence in every market. UKM Mart Teluk Pucung is one of the minimarkets to promote various kinds of products from small and medium business. This Community Empowerment Program (PKM) is to help small and medium business owners to debelop their businesses. The Business Model Canvas (BMC) method is one of the approaches in identifying business design. The implementation of BMC will provide a simple and comprehensive mapping of business models. The results of the BMC mapping will be used to find and understand the business model phenomenon in each member of UKM Mart. Assistance in creating BMC will make it easier for UKM owners to explain their business model to their business partners. They can measure the performance and effectiveness of their business model by conducting periodic evaluations. Business owners are able to identify the strengths and weaknesses of their business soo as to create new opportunities for their business development.